2008
DOI: 10.1111/j.1432-2277.2008.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of histologic findings on preimplant biopsy with kidney graft survival

Abstract: Summary Kidney biopsies are being used to evaluate marginal deceased donor organs, but, the literature on the utility of this practice remains conflicting. We re‐examined this issue by performing a multivariate analysis of 597 kidney transplant recipients. The presence of moderate arteriosclerosis and/or moderate arteriolosclerosis (MA), defined as ≥25% luminal compromise, was a significant predictor of graft outcome in standard criteria donors (multivariate, P = 0.01) and in expanded criteria donors (ECD) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 19 publications
(44 reference statements)
3
46
2
1
Order By: Relevance
“…The same happens with the other histologic compartments. Although some authors do not find any relationship of tubules, interstitium, and arteries with graft function [7,10,29], others do [8,11,28,31]. In our series, the overall biopsy score correlated with transplant outcome at all time points.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The same happens with the other histologic compartments. Although some authors do not find any relationship of tubules, interstitium, and arteries with graft function [7,10,29], others do [8,11,28,31]. In our series, the overall biopsy score correlated with transplant outcome at all time points.…”
Section: Discussionsupporting
confidence: 56%
“…Some groups found no relation between the percentage of glomerulosclerosis and renal function [31], although the majority consider it a very important parameter and discard kidneys with glomerulosclerosis of >20% [11,28] or even at lower values [7,8]. The same happens with the other histologic compartments.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In each case, at minimum three arterioles with a circular cross-section were selected, and their outer and inner circumferences were traced manually, followed by calculation of parameters including wall thickness and wall-to-lumen ratio [12]. A wall-to-lumen ratio ≥ 25% is classified as microangiopathy (arteriolosclerosis) [13]. We classified the changes as mild, moderate, and severe when the degree of luminal compromise was 25-30%, 31-50%, and >50%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Interpretation of a donor kidney biopsy, however, requires a meticulous evaluation of the degree of glomerulosclerosis, vessel arteriosclerosis, vessel hyalinosis, and interstitial fibrosis. Previous studies (3)(4)(5)(6)(7)(8)(9) have demonstrated considerable variability in biopsy findings based on the type of biopsy (wedge versus needle), sample size, experience of the pathologist, and inconsistency in reporting biopsy findings. Almost all the biopsies were evaluated by frozen section because they need to be read as soon as possible.…”
mentioning
confidence: 99%